Perilaku Keuangan Pengguna E-Wallet di Kudus: Financial Technology, Demografi, Literasi Keuangan Dan Lifestyle Sebagai Prediktor - Anindita Evelyn Jessica Putri; Audrey Jennifer Octavatiya (SMARTINDO, 2023)
Financial behavior of Indonesians people is still not in good category. Behavior which tends to be consumptive has an impact on irresponsible financial behavior such as not saving, much shopping until not preparing investmen funds. Technology advance can have an impact on people’s financial behavior. This study aims to analyze factors that can influence financial behavior, including Financial Technology, Demography, Financial Literacy and Lifestyle. With a quantitative approach, this study uses Structural Equation Modeling in the AMOS24 application. The following study used a sample of 180 respondents and obtained data from the results of questionnaires distributed using the Likert scale assessment method. The analysis in the following study used multiple linear regression. The result is Financial Technology has a significant positive effect on Financial Behavior, Demographics have a significant positive effect on Financial Behavior, Financial Literacy has no effect on Financial Behavior, and Lifestyle has a significant positive effect on Financial Behavior. Advice for digital wallet users to better understand and utilize FinancialTechnology, improve demographic conditions, understand theory and applying financial literacy, and improve lifestyle in order to make financial behavior better